1986
DOI: 10.1002/hlca.19860690719
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Pentafulvalen durch oxidative Kupplung von Cyclopentadienid mittels Kupfer(II)‐chlorid

Abstract: Synthesis of Pentafulvalene by Oxidative Coupling of Cyclopentadienide with Copper(I1) ChlorideStarting with a nearly quantitative coupling of cyclonondtetraenide 7 to 1, 1'-dihydrononafulvalene 8 by means of AgBF,, a simple general synthetic concept for fulvalenes is outlined (Scheme 2), consisting in an oxidative coupling of 'Huckel anions' like 2 and 7 to 1, 1'-dihydrofulvalenes 10 with Ag(1) or Cu(I1) salts, followed by deprotonation (-11) and oxidation (412); it has been realised in the case ofpentafulval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 20 publications
0
34
0
4
Order By: Relevance
“…Their matrix sample was compared to one of authentic 5 supplied by Doering and showed absorption maxima near 295 and 310 nm in the matrix; more recent studies give the maxima at 287, 299, 313 and 416 nm. [58] Subsequently, Baird et al demonstrated that photolysis of diazocyclopentadiene proceeds via cyclopentadienylidene that can be diverted to ketene in the presence of CO (Scheme 4). [63,64] The loss of nitrogen is irreversible and the detailed study confirmed that 5 does not arise from carbene addition to unchanged diazo compound; a UV band was recorded at 296 nm.…”
Section: Pentafulvalenes (Fulvalenes)mentioning
confidence: 97%
See 2 more Smart Citations
“…Their matrix sample was compared to one of authentic 5 supplied by Doering and showed absorption maxima near 295 and 310 nm in the matrix; more recent studies give the maxima at 287, 299, 313 and 416 nm. [58] Subsequently, Baird et al demonstrated that photolysis of diazocyclopentadiene proceeds via cyclopentadienylidene that can be diverted to ketene in the presence of CO (Scheme 4). [63,64] The loss of nitrogen is irreversible and the detailed study confirmed that 5 does not arise from carbene addition to unchanged diazo compound; a UV band was recorded at 296 nm.…”
Section: Pentafulvalenes (Fulvalenes)mentioning
confidence: 97%
“…[59] The reaction proves to be quite general and Cu II is often an alternative to Ag I . Thus the pathway of Scheme 1 can be markedly improved by using CuCl 2 in THF at -30°C for the cyclopentadienide coupling (dihydrofulvalene 14 is formed in 84 % yield) [58,71] and, after essentially quantitative deprotonation to 15 (BuLi), a second treatment with CuCl 2 and concentration provides a red solution (ca. 0.3 m) of spectroscopically pure 5.…”
Section: Pentafulvalenes (Fulvalenes)mentioning
confidence: 98%
See 1 more Smart Citation
“…[2,3] Wurden sie ursprünglich als Kuriositäten mit ungewçhnlichen Bindungslängen und -winkeln wahrgenommen, [4] werden Pentafulvalene mittlerweile als Liganden [5] für Übergangs-metalle sowie als Zwei-Elektronen-Akzeptoren unter Entstehung von aromatischen Dianionen verwendet. [6] Während unsubstituiertes Pentafulvalen instabil bei Temperaturen über À78 8C ist, [7] zeigt das perchlorierte Derivat vollständig reversible Redoxeigenschaften.…”
Section: Im Gedenken An Michael Bendikovunclassified
“…[7,8] Weitere Synthesen erfolgten mithilfe von Grignard-Additionen an Ketone [9] sowie der Homokupplung halogenierter Spezies mittels Über-gangsmetallen. [10] Auch Diazoverbindungen, die leicht molekularen Stickstoff freisetzen, sind mçgliche Ausgangsverbindungen.…”
Section: Im Gedenken An Michael Bendikovunclassified